Analysis of the Effect of Private Investment on Economic Growth in Palu City - Andi Herman Jaya (Institute of Computer Science (IOCS), 2022)
The economy experienced a period of negative growth means economic activity in this period has decreased. Palu-year period 2011-2021 economic growth fluctuations. These fluctuations can be influenced by private investment, Economic growth is one measure of the success of economic development in an area. Economic growth reflects economic activity. Economic growth can be positive and can also be negative. If the economy experienced a period of positive growth means economic activity during the period has increased. Whereas if years 2011-2021 are sourced from the Central Statistics Agency of North Sulawesi Province and Palu. The analytical method used is an econometric model single-log regression (log-log) with Ordinary Least Square (OLS). This study aims to determine whether the development of private investment affects the economic growth of the city of Palu. The data used using time series data period. The results of the regression model of economic growth with the regression equation is LPDRB = LINV 0.445. From these results show the development of private investment, direct expenditure and population positive and significant impact on economic growth of Palu.